Was Emergency Remote Education Enough To Save The Day? : Mathematics Teachers' Difficulties and Ways to Cope With These Difficulties - Vildan Donmuş Kaya; Ebru Kükey (Foxton Books, 2022)
This case study aims to examine the difficulties, and the ways to cope with these difficulties or the solution proposals for coping faced by middle school mathematics teachers during the Emergency Remote Education (ERE). The participants consisted of four online focus groups with eighteen mathematics teachers working in middle schools in Turkey. The data was collected semi-structured interviews. The data was analyzed the thematic approach. According to the findings, the teachers faced difficulties caused by students, teachers, infrastructure, schedule and curriculum, parents, and nature of mathematics. The difficulties were virtual classroom management, participation, and interest/motivation (caused by student), communication/interaction, measurement and evaluation, ICT competencies, and privacy (caused by teacher), device and internet deficiencies (caused by Infrastructure), supporting roles and supervising roles (caused by parents), Schedule and curriculum, and Nature of mathematics. Teachers were able to cope with difficulties by banning/restricting, contacting parents, paying attention to the arrangement of scheduled hours, making additional courses, sending additional lesson documents, and organizing different learning activities, rules, face-to-face homework checks, and face-to-face exams, adhering to the lesson time in the schedule determined by the school administration. The limitations of the study and implications for future research were discussed.